Beckwith-Wiedemann syndrome and isolated hemihyperplasia - Gomes, Marcus Vinícius de Matos; Ramos, Ester Silveira (São Paulo Medical Journal, 2003)
CONTEXT: Beckwith-Wiedemann syndrome is a complex and heterogeneous overgrowth syndrome with genetic and epigenetic alterations, involving genomic imprinting and cancer predisposition. Isolated hemihyperplasia is of unknown cause, and it may represent a partial or incomplete expression of Beckwith-Wiedemann syndrome. OBJECTIVES: A clinical and molecular review and proposal of the use of an experimental protocol to provide a practical approach for the physician. DATA SYNTHESIS: This review demonstrates the genetic and epigenetic mechanisms involved in the Beckwith-Wiedemann syndrome and isolated hemihyperplasia, and the candidate genes. To our knowledge, this is the first Brazilian protocol for research into these disorders. The results have been used at the Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo, to elucidate the basis of Beckwith-Wiedemann syndrome and isolated hemihyperplasia, and have been applied at the Hospital Universitário of the Faculdade de Medicina. CONCLUSIONS: Elucidation of the etiological mechanisms and use of a laboratory protocol to detect alterations in these disorders may be useful for guiding the management of such patients and genetic counseling of the families.